Gallium‐Based Liquid–Solid Biphasic Conductors for Soft Electronics - Reis Carneiro, Manuel (2023)
Soft and stretchable electronics have diverse applications in the fields of compliant bioelectronics, textile-integrated wearables, novel forms of mechanical sensors, electronics skins, and soft robotics. In recent years, multiple material architectures have been proposed for highly deformable circuits that can undergo large tensile strains without losing electronic functionality. Among them, gallium-based liquid metals benefit from fluidic deformability, high electrical conductivity, and self-healing property. However, their deposition and patterning is challenging. Biphasic material architectures are recently proposed as a method to address this problem, by combining advantages of solid-phase materials and composites, with liquid deformability and self-healing of liquid phase conductors, thus moving toward scalable fabrication of reliable stretchable circuits. This article reviews recent biphasic conductor architectures that combine gallium-based liquid-phase conductors, with solid-phase particles and polymers, and their application in fabrication of soft electronic systems. In particular, various material combinations for the solid and liquid phases in the biphasic conductor, as well as methods used to print and pattern biphasic conductive compounds, are discussed. Finally, some applications that benefit from biphasic architectures are reviewed.